Pengaruh Gaya Hidup dan Kepuasan Terhadap Loyalitas Pengguna Motor Harley Davidson di Kota Surabaya - Navi Muda Priyatna (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study examines the influence of lifestyle and satisfaction on user loyalty toward Harley-Davidson motorcycles in Surabaya, a metropolitan city with an active big bike rider community. The main issue addressed is how lifestyle impacts user loyalty, both directly and through the mediating role of satisfaction. The objective is to explore the causal relationships among lifestyle, satisfaction, and loyalty, and to assess satisfaction's mediating effect. A quantitative explanatory approach was employed, involving total sampling of 170 members from the Harley-Davidson Club Indonesia (HDCI) Surabaya. Data were collected via structured Likert-scale questionnaires and analyzed using multiple linear regression and the Sobel Test to assess mediation effects. The results indicate that lifestyle significantly affects both satisfaction (β=0.46) and loyalty (β=0.34), while satisfaction shows the strongest influence on loyalty (β=0.51). The Sobel Test confirms that satisfaction significantly mediates the relationship between lifestyle and loyalty. These findings suggest that user loyalty is not solely driven by product quality but also by emotional experiences, social involvement, and lifestyle symbolism associated with the Harley-Davidson brand. In conclusion, Harley-Davidson user loyalty in Surabaya is shaped by the synergy between lifestyle and perceived satisfaction. Marketing strategies that emphasize community experience and authentic lifestyle branding have proven effective in fostering long-term loyalty within this premium market segment.